(untitled) (Voice of Teacher, 2025)
This study has the fertility specifics of the Danuwar community in Nepal using the Bonga arts Stover proximate determinants framework with the view of establishing biological and behavioral pathways that govern fertility among the indigenous community in Nepal. National Total Fertility Rate (TFR) of Nepal is on the downward trend, indigenous and marginalized communities are still experiencing unique reproductive dynamics due to early marriage, low autonomy and cultural practices. The women sexuality, contraceptive use, postpartum insusceptibility, and sterility using the data of 289 women in Godawari Municipality aged between 15-49 years. The exposure to marriage (Cm), contraception (Cc), postpartum in fecundability (Ci) and abortion (Ca) indices were computed in line with the Bonga arts procedures. The contraceptive prevalence of 78.8 led to contraception index of 0.370 and the long-term breastfeeding, with an average of 30.6 months, was associated with a postpartum infecundacy index of 0.41. Conversely, the marriage rate (Cm = 0.994) was nearly universal, which the patterns of marriage did not furnish much fertility control, and as such, this carried on the patterns of early and universal marriages. There was a calculated value of 0.0 because there was no reported data on the effect of abortion. The model based TFR of 2.29 births per woman is close to Nepal national TFR of 2.1. On the whole, the findings indicate that the interactions of the contemporary contraceptive behavior and the traditional practice of breastfeeding is the main to fertility control in the Danuwar community. The results highlight the need of culturally sensitive reproductive-health programs targeting indigenous people.